Perlindungan Ham Terhadap Lansia Korban Selamat Atas Kebrutalan Tragedi 1965 - Aisha Rachmadian Puteri (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The 1965 Tragedy left quite deep wounds on the entire Indonesian nation. Despite the large number of victims who fell, there are certainly also survivors who survived and are still alive today. Those who survived have now become elderly people who need adequate protection and services, but are receiving treatment that they do not deserve as elderly people. The purpose of this writing is to find out how Human Rights Protection for the elderly is realized, especially survivors of the 1965 Tragedy. This writing uses a literature study method with a normative approach. The results that the author found are that Human Rights Protection for the elderly is relatively low due to discrimination by other communities and the attitude of the current younger generation which is quite arrogant towards the elderly.